Primitive Christianity reviv'd: in four volumes ... - Whiston, William (Printed for the author, 1711)
Vol. I. Epistles of Ignatius, both larger and smaller, in Greek and English. -- Vol. II. The Apostolical constitutions, in Greek and English. -- Vol. III. An Essay on those Apostolical constitutions. -- Vol. IV. An Account of the primitive faith, concerning the Trinity and incarnation.